Participation, Social Accountability and Transparency Mechanisms in Development Policy Loans in Latin America, 2000-2003 - Reuben, William; Arévalo, Blanche (World Bank, Washington, DC, 2012)
A document review of development policy lending projects in the Latin America and Caribbean Region, approved in fiscal years (FY) 2000-03 at the World Bank, reveals increasing civil society involvement in loan design and goals, context, and activities supported by the loans. This study examines the tools used by the World Bank to promote public transparency, community participation, social auditing, and accountability in development policy lending during the past four years, and assesses the extent to which these objectives have been met.